Language Variation in the Dubbing Into English of the Netflix Series Baby (2018–2020) and Suburra: Blood on Rome (2017–2020) - Bonella, Laura (Íkala, Revista de Lenguaje y Cultura, 2023)
Although standard Italian is taught from primary school and is widely prevalent in the media, dialects are still spoken in many households all over the country. This trend is captured by many popular video-on-demand providers such as Netflix and HBO, who are diversifying their offer by promoting their own non-English language productions via both subtitling and dubbing. This article analyses how language variation, particularly in the form of dialect and slang, is adapted for dubbing in the Italian Netflix series Baby (2018‒2020) and Suburra: Blood on Rome (2017–2020). Specifically, it examines the most common translational strategies that have been implemented in the dubbing of both series in English. In particular, dialectal elements are often translated directly or generalised, at times, with the addition of taboo words. Correspondingly, youth jargon is largely translated via direct translations or creative additions. Despite having two different age groups at the centre of the narration, similar translation strategies were used in the two series. The qualitative analysis demonstrates that dialect is used to define social disparity, since characters involved with criminality speak principally dialect whereas wealthy students, affluent characters, politicians, and churchmen draw on standard Italian primarily.